(untitled) (Journal of Parents and Teachers, 1996)
It raises parental concerns about how television and advertising affect children, highlighting the social hypocrisy surrounding pornography and violence. It is crucial that children discuss these scenes with their parents using their own language. Parents are also called upon to take an active role in selecting the content their children consume.